Mutational analysis of glycyl-tRNA synthetase (GARS) gene in Hirayama Disease - Blumen, Sergiu C. (2010)
Sporadic juvenile muscular atrophy of the distal upper extremity or Hirayama's Disease (HD) and autosomal dominant motor distal neuronopathy/axonopathy (CMT2D/dSMA-V), produced by glycyl-tRNA synthetase (GARS) gene mutations, share some clinical features including: young age of onset, predilection for the distal upper extremity, asymmetry, sparing of proximal muscles and unusual cold sensitivity. However, incomplete penetrance of GARS gene mutations may account for apparently non-familial cases. In order to inquire whether GARS gene mutations are associated with HD we studied seven patients fulfilling the clinical and electrodiagnostic criteria for HD. All patients underwent MRI of cervical spine that excluded compressive myelopathy in neutral position and intramedullary pathology. Each patient was tested for the presence of mutations in GARS by sequencing all coding exons amplified from genomic DNA. No pathogenic mutations were found, excluding the role of GARS gene as a possible factor in the etiology of HD in this cohort.